Complement C5a Induces Pro-inflammatory Microvesicle Shedding in Severely Injured Patients - Karasu, Ebru; Demmelmaier, Julia; Kellermann, Stephanie; Holzmann, Karlheinz; Köhl, Jörg; Schmidt, Christoph Q.; Kalbitz, Miriam; Gebhard, Florian; Huber-Lang, Markus S.; Halbgebauer, Rebecca (Frontiers in Immunology, 2020)
Initially underestimated as platelet dust, extracellular vesicles are continuously gaining interest in the field of inflammation. Various studies addressing inflammatory diseases have shown that microvesicles (MVs) originating from different cell types are systemic transport vehicles carrying distinct cargoes to modulate immune responses. In this study, we focused on the clinical setting of multiple trauma, which is characterized by activation and dysfunction of both, the fluid-phase and the cellular component of innate immunity. Given the sensitivity of neutrophils for the complement anaphylatoxin C5a, we hypothesized that increased C5a production induces alterations in MV shedding of neutrophils resulting in neutrophil dysfunction that fuels posttraumatic inflammation. In a mono-centered prospective clinical study with polytraumatized patients, we found significantly increased granulocyte-derived MVs containing the C5a receptor (C5aR1, CD88) on their surface. This finding was accompanied by a concomitant loss of C5aR1 on granulocytes indicative of an impaired cellular chemotactic and pro-inflammatory neutrophil functions. Furthermore, in vitro exposure of human neutrophils (from healthy volunteers) to C5a significantly increased MV shedding and C5aR1 loss on neutrophils, which could be blocked using the C5aR1 antagonist PMX53. Mechanistic analyses revealed that the interaction between C5aR1 signaling and the small GTPase Arf6 acts as a molecular switch for MV shedding. When neutrophil derived, C5a-induced MV were exposed to a complex ex vivo whole blood model significant pro-inflammatory properties (NADPH activity, ROS and MPO generation) of the MVs became evident. C5a-induced MVs activated resting neutrophils and significantly induced IL-6 secretion. These data suggest a novel role of the C5a-C5aR1 axis: C5a-induced MV shedding from neutrophils results in decreased C5aR1 surface expression on the one hand, on the other hand it leads to profound inflammatory signals which likely are both key drivers of the neutrophil dysfunction which is regularly observed in patients suffering from multiple traumatic injuries.